2019
DOI: 10.1080/13561820.2019.1593116
|View full text |Cite
|
Sign up to set email alerts
|

Communication about patients during ward rounds and verbal handovers: A gender perspective

Abstract: This article investigates gender patterns on how two interprofessional teams communicate about patients in their absence. Thirteen ward rounds and 17 verbal handovers were audio-recorded and analyzed through a qualitative content analysis. The ward rounds consisted of 1 physician and 2-4 nurses. The verbal handovers consisted of 2-3 nurses and as many assistant nurses. The data were collected at a cardiac clinic at a hospital in southern Sweden. The results indicate that when patients acted according to social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…These recommendations are not only relevant to people who define themselves as nonbinary but reflect more general cultural shifts about how people think about and express their gender identities (see also Klein 2011). Hedegaard (2019) studied medical personnel interacting with patients and found that when patients did not follow stereotypically gendered norms, the staff interacted differently with them (more informally, less "professionally"). Hildenbrand, Perrault, and Rnoh (2022) found that female patients were more likely to feel they were treated dismissively by healthcare providers than male patients.…”
Section: Literature Review Gender/ing Language and Communicationmentioning
confidence: 99%
“…These recommendations are not only relevant to people who define themselves as nonbinary but reflect more general cultural shifts about how people think about and express their gender identities (see also Klein 2011). Hedegaard (2019) studied medical personnel interacting with patients and found that when patients did not follow stereotypically gendered norms, the staff interacted differently with them (more informally, less "professionally"). Hildenbrand, Perrault, and Rnoh (2022) found that female patients were more likely to feel they were treated dismissively by healthcare providers than male patients.…”
Section: Literature Review Gender/ing Language and Communicationmentioning
confidence: 99%
“…In psychiatric practice in particular, such handovers and rounds are central in producing knowledge about patients, whose mental states are assessed during observations of their behaviour, activities and speech, all of which depend upon context (Buus, 2006; Eivergård, Enmarker, Livholts, Aléx, & Hellzén, 2018; Scovell, 2010). In verbal handovers and ward rounds, language plays an important role as a tool for conveying information (Hedegaard, 2019; Salzmann‐Eriksson, 2018). However, in those contexts, language should not be conceived as a simple way of objectively transferring information but as a convention of social groups.…”
Section: Introductionmentioning
confidence: 99%
“…By extension, knowledge should be understood as the effect of power constituted in language (Crowe, 1998; Foucault, 1994). In language as such, gender operates as an overall categorising principle (Hedegaard, 2019; Kumpula, Gustavsson, & Ekstrand, 2018; Mercer & Perkins, 2014; Perron & Holmes, 2011). For that reason, the perceptions of patients in general are constructed from normative, context‐bound perspectives about how women and men should behave, act and talk (Eivergård et al., 2018; Hamilton & Manias, 2006)—that is, how they should or do perform gender (Butler, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations